P56 A rare case of Sjögren's nephropathy. (20th April 2020) - Amoasii, Constanta; Benson, Rosalind; Harper, Janice; Mewar, Devesh
Abstract: Background: A presentation of acute kidney injury (AKI) in a patient with a longstanding diagnosis of SLE nephritis was challenged following unexpected renal biopsy and immunology resulting in a diagnosis of primary Sjögren's Syndrome (pSS) related fibrillary glomerulonephritis (FGN). Methods: A 62 year old Caucasian female presented with AKI and infected leg ulcer. Previously diagnosed with SLE (1996), anti-phospholipid syndrome and non-biopsy proven lupus nephritis (LN), CKD stage G2/3 she was on Hydroxychloroquine and lifelong anticoagulation. Examination revealed bilateral pitting oedema up to knees and a large non healing skin ulcer to left knee. Investigations showed new anaemia (Hb 75g/dl, MCV 94), lymphopaenia, urea- 25 (9.8), Creatinine- 280 (97), urine protein 6.88g/24 hr. USS KUB, ECHO, CXR, virology screen, PET CT were unremarkable. Immunology studies revealed ANA 1:160, anti-Ro, anti-La, but normal DsDNA and C3, C4. In the light of reported sicca symptoms and serology the diagnosis was revised to pSS. Renal biopsy was initially reported as diffuse lupus nephritis (Class IV) with crescents, and focal weak mesangial IgG and C3 but no glomerular deposits. Electron microscopy (EM) demonstrated abundant mesangial and intramembranous deposits with a fibrillary substructure diagnostic of FGN. Immunosuppression with pulsed intravenous (IV) methylprednisolone and IV Cyclophosphamide were given. She developed acute arterial intercostal bleeding at biopsy site and further significant lower gastrointestinal bleeding unamenable to endoscopic therapy or embolisation and the patient died. Results: This case highlights the importance of ensuring that serology is interpreted correctly alongside histopathology and urinalysis in the diagnosis of CTD related renal disease. PSS related nephropathy is seen in less than 10% of patients. Tubulointerstitial nephritis (TIN) accounts for 2/3 of patients and glomerulonephritis (GN), typically membranoproliferative GN (MPGN) for most others. FGN in pSS is very rare, with only 3 reported cases to date. Like lupus nephritis, FGN can present with AKI, hypertension and nephrotic range proteinuria. However, renal biopsy proves invaluable in differentiating between the conditions. In FGN characteristically on biopsy disorganised, non-branching fibrils are seen in all glomerular compartments and are negative for congo red stain further differentiating from amyloid FGN. Immunofluorescence microscopy shows uniform staining of the fibrils for immunoglobulins (mostly subclass IgG4). FGN has a poor prognosis with patients developing severe chronic renal failure despite immunosuppression. Conclusion: Considering surprising investigation results, it is crucial we rechallenge the validity of longstanding diagnoses as highlighted by our case. In proven pSS with systemic features we recommend screening all patients for renal disease annually including serum electrolytes, urine dipstick, protein creatinine ratio and pH. If abnormalities are identified, renal US and consideration of biopsy is crucial in establishing aetiology as management and prognosis differs between subtypes. Disclosures: C. Amoasii None. R. Benson None. J. Harper None. D. Mewar None.